A Study on the Effect of Tourism Development Cognitive Factors on the Attitudes of Local Stakeholders - Young-Hoon Lee, Song-Heui Oh, Jae-Young Park (International Journal of Advanced Science and Technology, 2020)
Background/Objectives: The purpose of this study is to improve the mountain tourism development environment by analyzing the effects of tourism development awareness factors on tourism development attitudes.